1988
DOI: 10.1159/000116241
|View full text |Cite
|
Sign up to set email alerts
|

Transient Global Amnesia: Pathogenesis and Prognosis

Abstract: Fifty-five patients admitted to hospital for ‘pure’ transient global amnesia (TGA) were studied and followed up for a period ranging from 12 to 67 months. The major pathogenetic theories of TGA (epileptic, thrombotic and migrainous) were investigated through the study of clinical histories and risk factors and the recurrences of neurological disturbances during follow-up. Seventy-one percent of the sample had one or more thrombotic risk factors (TRF), 2 patients had both TRF and a history of migraine, and none… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 13 publications
3
5
0
Order By: Relevance
“…Both our RIA and lacunar syndrome patient groups showed a significantly worse prognosis than TGA sub jects. On the other hand, the large majority of studies on the long-term prognosis of subjects with T1A have shown a higher mortality than that of the general population [44], Our results completely agree with the conclusions of all recent long-term follow-up studies on TGA survival rate which adopted analogous inclusion and exclusion cri teria [28][29][45][46], The hypothesis that TGA could be considered as a focal ischemic cerebrovascular disease has not received any support from such studies. The same conclusion emerges from our findings on the occurrence of stroke, RIA and vascular death.…”
Section: Discussionsupporting
confidence: 89%
“…Both our RIA and lacunar syndrome patient groups showed a significantly worse prognosis than TGA sub jects. On the other hand, the large majority of studies on the long-term prognosis of subjects with T1A have shown a higher mortality than that of the general population [44], Our results completely agree with the conclusions of all recent long-term follow-up studies on TGA survival rate which adopted analogous inclusion and exclusion cri teria [28][29][45][46], The hypothesis that TGA could be considered as a focal ischemic cerebrovascular disease has not received any support from such studies. The same conclusion emerges from our findings on the occurrence of stroke, RIA and vascular death.…”
Section: Discussionsupporting
confidence: 89%
“…, 1986; Gandolfo et al. , 1992) but in line with others (Colombo and Scarpa, 1988; Guidotti et al. , 1989; Zorzon et al.…”
Section: Discussionsupporting
confidence: 85%
“…Their mean age was 59 years, mean duration of disease 12 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) years, mean duration of levodopa therapy 9 5 (1 5-19) years and mean stage of Hoehn and Yahr 3-4 when "off" and 2-4 when "on". All patients were known to respond to their first morning dose of 100 or 200 mg of oral levodopa plus decarboxylase inhibitor within 15 to 30 minutes and the mean duration of effect was 135 (90-120) minutes.…”
Section: Subcutaneous and Sublingual Levodopa Methyl Ester In Parkinsmentioning
confidence: 99%